The Collaborative Economy in Action: European Perspectives - Andrzej Klimczuk; Vida Česnuitytė; Gabriela Avram (University of Limerick, 2021)
The book titled The Collaborative Economy in Action: European Perspectives is one of the important outcomes of the COST Action CA16121, From Sharing to Caring: Examining the Socio-Technical Aspects of the Collaborative Economy (short name: Sharing and Caring; sharingandcaring.eu) that was active between March 2017 and September 2021. The Action was funded by the European Cooperation in Science and Technology - COST (www.cost.eu/actions/CA16121). The main objective of the COST Action Sharing and Caring is the development of a European network of researchers and practitioners interested in investigating the collaborative economy models, platforms, and their socio-technological implications. The network involves scholars, practitioners, communities, and policymakers. The COST Action Sharing and Caring helped to connect research initiatives across Europe and enabled scientists to develop their ideas by collaborating with peers. This collaboration opportunity represented a boost for the participants' research, careers, and innovation potential. The main aim of this book is to provide a comprehensive overview of the collaborative economy (CE) in European countries with a variety of its aspects for a deeper understanding of the phenomenon as a whole. For this reason, in July 2017, an open call for country reports was distributed among the members of the COST Action Sharing and Caring. Representatives of the member countries were invited to produce short country reports covering: definition(s) of the CE; types and models of the CE; key stakeholders involved; as well as legislation and technological tools relevant for the CE. Submitted reports varied in length and regarding the level of detail included, in accordance with how much information was available in each respective country at the time of writing. Editors of the book have compiled these early reports into a summary report, which was intended as a first step in mapping the state of the CE in Europe. The Member Countries Report on the Collaborative Economy, edited by Gaia Mosconi, Agnieszka Lukasiewicz, and Gabriela Avram (2018) that was published on the Sharing and Caring website, represented its first synergetic outcome and provided an overview of the CE phenomenon as interpreted and manifested in each of the countries part of the network. Additionally, Sergio Nassare-Aznar, Kosjenka Dumančić, and Giulia Priora compiled a Preliminary Legal Analysis of Country Reports on Cases of Collaborative Economy (2018). In 2018, after undertaking an analysis of the previous reports' strengths and weaknesses, the book editors issued a call for an updated version of these country reports. Prof. Ann Light advised the editorial team, proposing a new format for country reports and 4000 words limit. The template included: Introduction, Definition, Key Questions, Examples, Illustration, Context, Developments, Issues, Other Major Players, and Relevant Literature. The new template was approved by the Management Committee in October 2018. The task force that had supported the production of the first series of country reports (Dimitar Trajanov, Maria del Mar Alonso, Bálint Balázs, Kosjenka Dumančić, and Gabriela Avram) acted as mentors for the team of authors in each country. The final reports arrived at the end of 2018, bringing the total number of submissions to 30 (twenty-nine European countries plus Georgia). A call for book editors was issued, and a new editorial team was formed by volunteers from the participants of the COST Action: Andrzej Klimczuk, Vida Česnuityte, Cristina Miguel, Santa Mijalche, Gabriela Avram, Bori Simonovits, Bálint Balázs, Kostas Stefanidis, and Rafael Laurenti. The editorial team organized the double-blind reviews of reports and communicated to the authors the requirements for improving their texts. After reviews, the authors submitted updated versions of their country reports providing up-to-date interdisciplinary analysis on the state of the CE in 2019, when the reports were collected. During the final phase, the chapters were again reviewed by the lead editors together with all editorial team members. At the time, the intention was to update these reports again just before the end of the COST Action Sharing and Caring in 2021 and to produce a third edition. However, the COVID-19 pandemic changed these plans. Thus, this final volume was created by 82 scholars-editors and contributors-and consists of reports on 27 countries participating in the COST Action.
Keywords: D83; D16; Z18; 330; Collaborative Economy; Shared Consumption; Sharing Economy; Platform Capitalism; Legal Regulations; Fair Economy